High Speed flywheel and test rig design for rural energy storage - Okou, Richard (Department of Electrical Engineering, 2014)
There is considerable growth in the renewable energy sector to contribute to sustainable development, environmental conservation and most importantly to provide affordable energy to isolated rural communities of sub-Saharan Africa. Renewable energy sources such as solar and wind require energy storage since the source of energy is intermittent. Electrochemical batteries especially from lead acid are commonly used to store energy in Solar Home Systems (SHS) for rural electrification in sub-Saharan Africa. Disadvantages such as low efficiencies, low life cycle costs, high maintenance, comparatively short life and serious environmental and human toxicity effects exist. Since recycling is not widespread, replacement costs are high, as are the resultant environmental damage and health hazards from lead and sulphuric acid. In this thesis, an electromechanical flywheel energy storage device is proposed as an alternative to a lead acid battery in order to increase efficiency, life expectancy, increased high depth of discharge, low life cycle cost and elimination of adverse environmental effects. Due to income and service skill constraints in rural areas, the proposed, high speed flywheel systems (for long time energy storage) will require the use of low cost configurations and topologies, special considerations on the flywheel rotor profile design, robust electrical machines, simple power electronics and a low cost bearing set. Low loss magnetic bearings are also possible but were limited by time while also making their maintenance complex especially in rural areas. Conventional high strength composite materials used in flywheel rotor manufacture for high speed operation are expensive. Therefore there is a need to develop techniques to profile the rotor shape so as to improve on material usage and exhibit lower mechanical stresses. A robust electrical machine topology for high speed operation and a simple drive system are investigated to ensure simple assembly, low cost and low maintenance. vii The various flywheel components were designed using analytical and numerical methods. Two techniques were used to develop two optimal profiles for the flywheel rotor structure. Partial differential equations and analytical solutions were employed to develop the profiles. Analytical equations were used to design the electrical machine, drive, bearing system and other accessories. The final electromechanical battery prototype consisted of a composite flywheel rotor made from E-glass fibre materials, double rotor Axial Flux Permanent Magnet (AFPM) machine and a drive system using Brushless DC (BLDC) mode of operation. The system was designed for 300Wh of energy storage for the delivery of 100W and 500W of power and an operating speed range of 8,000 rpm-25,000 rpm. The design and development of the flywheel energy storage system and test rig using locally available materials was investigated. Experiments were conducted for speeds up to 6,000 rpm. The electromechanical battery was able to store a maximum of 77Wh of energy. The shortfall of the system to meet its design specifications was investigated and found to have been caused by vibrations resulting from prototyping issues. A thermal model was developed to predict the temperature rise in the system which showed a good correlation with the experimental results.